Factor Analysis of Women's Empowerment in Tantri Class Participation for High Risk Pregnant Women - Rina Kartikasari; Putry Hilda Tariany; Susi Irianti; Ayu Kurnia Anggraeni (PROFESSIONAL HEALTH JOURNAL, 2025)
Classes for pregnant women are an effort to detect high-risk pregnantwomen that began to be socialized since 2010 in Indonesia, Puskesmas Ciruas has a class for high-risk pregnant women called Tantri (Temukan Analisa Tatalaksana Ibu Hamil dan Nifas Resiko tinggi). This study aims to determine the factors of women's empowerment in the participation of Tantri classes for high-risk pregnant women in the Ciruas Health Center Working Area in 2024. The method used in this research is Mixed Methods. The number of samples in this study were 79 respondents using total sampling. Data analysis using Chi Square test and concurrent triangulation. The results showed 43 respondents (54.4%) had poor participation in Tantri class, there was a relationship between knowledge (Pv=0.013; OR 7.4), occupation (Pv=0.000; OR 11.4), and social support (Pv=0.002; OR 5.8), with Tantri class participation. The data was supported by qualitative research through in-depth interviews with 5 informants. There is no relationship between well-being of pregnant women with Tantri class participation (α> 0.05) the results of the interview revealed that well-being makes it easier for pregnant women to understand reality by emphasizing self-confidence so that mothers always participate in Tantri class. It is recommended for the practice site to make a policy for high-risk pregnant women so that husbands participate in Tantri class at least once during the Tantri class and create an online forum for high-risk pregnant women who work.